Avaliação cinemática de variáveis relacionadas ao resultado dos saltos de potros - Fernanda Nascimento de Godoi (2012)
This study was carried out to estimate the repeatability of variables associated with the performance of yearling at jumping and predict the likelihood of success on the jump using linear and angular characteristics of the yearlings at station and jumping. Yearlings (n=109) of the Brazilian Army were evaluated with anatomical landmarks highlighted with reflective markers. The yearlings were filmed in station and during five jumps of vertical fence with 0.60, 0.80 and 1.05 meters higher, at the 22-25, 23-32 and 36-39 months of age, respectively. The images were obtained with camera acquisition frequency of 100 Hz and analyzed with Simi Reality Motion Systems®. The estimated values of repeatability on jumping were smaller at first assessment, when the animals were younger and height of the fence was smaller, and higher in the last evaluation, at 36-39 months of age, when the yearlings have had performed the experimental protocol and fence height was increased. The results used in a logistic model were selected by a previous analysis of principal components and used as independent variables. The linear characteristics of yearlings at station with 22-25 months of age, only the age of the yearling was significant source of variance, while the angular characteristics, the angle of the neck and age of the animals at the time of evaluation were significant in the model prediction. The significant variables in the model of the yearling jumping were: length of stride prior to the fence, take-off distance, height of forelimb point of hoof over the fence and velocity of stride over the fence, velocity of stride over the fence, humerus-radial vertical distance of forelimb fetlock, head angle, neck angle, femoro-tibial angle, withers-croup-hind limb fetlock angle and stifle-fetlock vertical distance. The results indicate that for a successful jump is necessary reduce the length of stride prior to the fence and increasing take-off distance and providing a higher height of forelimb point of hoof. Moreover, the yearling must overcome the fence at a slower speed, make more flexed forelimbs and hind limbs also present a greater femoro-tibial angle. The angles of the head and neck of the yearlings were important to the success of the jump, lower values being desired for greater efficiency of the jump.